The Impact of CO₂ Emissions on International Tourism Performance: An Empirical Study on G20 Member Countries - Ibnu Hajar; Maimun Maimun; Zhafirah Rizqa Farhan (Hasanuddin Economics and Business Review, 2026)
This study examines the effect of CO₂ emissions on international tourist arrivals in G20 member countries, with particular attention to the underexplored reverse channel through which environmental degradation may weaken tourism performance. The study positions the CO₂–tourism relationship within the broader agenda of low-carbon development and sustainable tourism competitiveness. This study employs balanced panel data covering 19 G20 member countries from 2014 to 2019. Pooled OLS, Fixed Effect, and Random Effect models are estimated, while the Chow Test, Hausman Test, and Breusch–Pagan Lagrange Multiplier Test are used to determine the most appropriate model. The Fixed Effect Model is selected as the preferred specification to control for unobserved time-invariant country characteristics. The results show that CO₂ emissions are negatively and significantly associated with international tourist arrivals. A one percent increase in CO₂ emissions is linked to a 0.625 percent decline in inbound tourism, suggesting that environmental degradation may reduce destination attractiveness. GDP per capita is the strongest positive correlate of tourism performance, while trade openness and real effective exchange rate appreciation are negatively associated with tourist arrivals. Population size is not statistically significant in the fixed effect specification. This study contributes to the tourism-environment literature by examining the reverse effect of CO₂ emissions on tourism performance using G20 countries as a unified analytical context. The findings offer policy-relevant insights for low-carbon tourism governance, sustainable destination competitiveness, and green development strategies in advanced and emerging economies.